Wczesnoszkolne nauczanie języków obcych – polskie prace empiryczne w świetle aktualnych dyskusji o badaniach przyswajania języka obcego przez dzieci - Andrzejewska, Ewa (Neofilolog, 2010)
The introduction of compulsory teaching of a foreign language in the early years of education is the most important development in recent accounts of foreign language teaching. The identification of the early start is accompanied by attempts to obtain empirically based concepts aiming to show how to teach children in school conditions in the most effective way. Last 10 years witnessed a considerable progress in the area of learning and teaching foreign languages by/to children. This article presents Polish empirical studies in the light of contemporary research related to teaching a foreign language in the early years of education.